Предмет: Алгебра,
автор: Лизавета183
(a-6)(a+5)(a-1)-(aa-2a)(a+1)
Упростите выражение, пожалуйста)))
Ответы
Автор ответа:
0
(a-6)(a+5)(a-1)-(aa-2a)(a+1)=(а²+5а-6а-30)(а-1)-(а³+а²-2а²-2а)= (а²-а-30)(а-1)-а³+а²+2а=а³-а²-а²+а-30а+30-а³+а²+2а=-а²-27а+30
Автор ответа:
0
(a - 6)(a + 5)(a - 1) - (a^2 - 2a)(a + 1) =
= (a^2 + 5a - 6a - 30)(a - 1) - (a^3 + a^2 - 2a^2 - 2a) =
= (a^2 - a - 30)(a - 1) - (a^3 - a^2 - 2a) =
= a^2 (a - 1) - a (a - 1) - 30(a - 1) - a^3 + a^2 + 2a =
= a^3 - a^2 - a^2 + a - 30a + 30 - a^3 + a^2 + 2a =
= - a^2 - 27a + 30 = - (a^2 + 27a - 30)
= (a^2 + 5a - 6a - 30)(a - 1) - (a^3 + a^2 - 2a^2 - 2a) =
= (a^2 - a - 30)(a - 1) - (a^3 - a^2 - 2a) =
= a^2 (a - 1) - a (a - 1) - 30(a - 1) - a^3 + a^2 + 2a =
= a^3 - a^2 - a^2 + a - 30a + 30 - a^3 + a^2 + 2a =
= - a^2 - 27a + 30 = - (a^2 + 27a - 30)
Похожие вопросы
Предмет: Английский язык,
автор: sambo8027
Предмет: Математика,
автор: sanechka222007
Предмет: Алгебра,
автор: savatinao
Предмет: Алгебра,
автор: seaofgloss
Предмет: Алгебра,
автор: hojiya